CTD313 profiles during MOSES Sternfahrt 5 - Götz Flöser; Martina Heineke (PANGAEA, 2025)
Nutrients, carbon species such as POC, DIC, DOC, pCO2 were sampled, and vertical profiles using CTDs with temperature, salinity, pressure, oxygen, pH, turbidity and fluorescence sensors were deployed in an area mostly between the Elbe estuary and Helgoland during the MOSES (https://www.ufz.de/moses/) Stern-5 between Aug. 31st and Sep 3rd, 2020. The research vessel Ludwig Prandtl covered the area between 53.9 N 7.88 E and 54.75 N 8.7 E. The purpose of the MOSES project is to be prepared for an extreme event like a flood or drought in the Elbe or Weser River. In order to calculate the difference in nutrient, carbon or other concentrations it is necessary to monitor the extquotesinglenormal extquotesingle state of the system. Water samples were collected using the three sampling cylinders of the Sea&Sun CTD313. The sample water was withdrawn from the cylinders, processed in the lab container on board and stored in the fridge or deep-freezer. The CTD measured vertical profiles at every station from the water surface to 2 m above ground.